On The Modified Divergence Information Criterion - Naser, J. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
In this work (paper), we investigate about the robustness of the modified divergence Information Criterion (MDIC), which proposed by Mantalos, Mattheou and Karagrigoriou (2008), to determine the probability of the Criterion picking up the true lag for Autoregressive process, when the error term of this process is normally and Non normally distributed. We obtained the results for different sample sizes by using simulation.